Fabrication of naturally derived scaffolds using indirect rapid prototyping techniques - Ng, Zhen Yang. (2009)
For the past decade, tissue engineering has emerged rapidly as a promising alternative method to solve health problems, by means of repairing or replacing damaged tissues or organs. There are many progresses made on the methods and biomaterials used, to manufacture scaffolds with porous structure and nutrient rich environment that favour the growth of the tissue within the scaffolds. Due to the limitation of traditional fabrication techniques, which could not control the porous geometry, advanced manufacturing technologies, such as Rapid Prototyping techniques have been developed, to aid in overcoming the limitations.